The Role of Inoculation with Glomus macrocarpum and Saprophytic Fungi on Growth of Wheat Plant Grown in Addition with Olive Mill Residues - Banni, Abdulhakim S. (Scientific Journal for Faculty of Science-Sirte University, 2022)
This study was carried out to test the influence of olive mill dry residue (DOR), Aqueous extraction (ADOR) and (SDOR) fraction treated with saprobe fungi on growth of Wheat (Triticum aestivum L.) plants colonized by G. macrocarpum.These fungal genera Aspergillus niger and Penicillium crustaceum were reported to possess the ability of detoxifying by degrading its phenolic compounds found in olive mill dry residue (ADOR and SDOR) ) fraction . The percentage of mycorrhizal colonization by G. macrocarpum strongly decreased in presence of DOR, but the level of AMF colonization likewise increased in presence of ADOR or SDOR. Our study demonstrates that, in controlled conditions, The use of certain saprobe and AM fungi allows the possibility of using DOR as an organic fertilizer.